Haemodynamic and myocardial metabolic effects of captopril in chronic heart failure. - Chatterjee, K (1982)
In 15 patients with chronic left ventricular failure caused by ischaemic heart disease, cardiac output and right heart pressures were measured before and after the oral angiotensin-converting enzyme inhibitor, captopril, which was administered in increasing doses. In 12 of 15 patients, coronary blood flow, and in 11 patients myocardial oxygen extraction and consumption and lactate extraction were also determined before and after captopril therapy. Cardiac index and stroke volume index increased by an average of 25% and 27%, respectively. Pulmonary capillary wedge pressure also decreased in all patients (average 27%), suggesting improved left ventricular function. The rate-pressure product, coronary blood flow, and myocardial oxygen consumption decreased significantly; in one of 11 patients there was myocardial lactate production, despite decreased myocardial oxygen demand and consumption. These findings suggest that in patients with chronic heart failure, improved left ventricular function with captopril is generally associated with decreased metabolic cost and that deterioration of metabolic function occurs infrequently.